Leading from the second chair : serving your church, fulfilling your role, and realizing your dreams - Bonem, Mike, 1959-; Patterson, Roger, 1972- (San Francisco : Jossey-Bass, 2005)
Leading from the Second Chair offers an invaluable resource to leaders who serve in second (and third and fourth) chair roles, enabling them to become more productive, proactive, and fulfilled. The book reveals the paradoxes of second chair leadership. These leaders must be subordinate to the top leader yet lead in their own right. They should be deep in their expertise but wide in perspective. And they must be content in their jobs yet remain enthusiastic about their dreams for the future.
Living in the paradoxes -- Am I a second chair leader? -- Taking it from the top -- Crossing the line -- A matter of perspective -- Building the team-- one relationship at a time -- Putting it into practice -- Contentment in the second chair -- Dreaming in the second chair -- Leaving the second chair -- A word to first chairs on the contentment-dreaming paradox.
Includes bibliographical references (p. 177-178) and index.
Keywords: Christian leadership; Leadership -- Religious aspects -- Christianity